2012
DOI: 10.1111/pbi.12030
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of OsSIZ1, a rice SUMO E3 ligase, enhances broad abiotic stress tolerance in transgenic creeping bentgrass

Abstract: SummarySumoylation is a posttranslational regulatory process in higher eukaryotes modifying substrate proteins through conjugation of small ubiquitin-related modifiers (SUMOs). Sumoylation modulates protein stability, subcellular localization and activity; thus, it regulates most cellular functions including response to environmental stress in plants. To study the feasibility of manipulating SUMO E3 ligase, one of the important components in the sumoylation pathway in transgenic (TG) crop plants for improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 87 publications
4
84
0
Order By: Relevance
“…As SIZ proteins are also conserved in plants (Figure 3), it is likely that the heterologous overexpression of SIZ enhances cold tolerance in plants. Recently, it was reported that the expression of rice OsSIZ1 resulted in tolerance to drought and heat stresses and phosphate starvation in creeping bentgrass (Li et al 2013). Although cold tolerance was not investigated in that study, it is likely that OsSIZ1 also enhances cold tolerance, as we observed for SIZ1 (Figure 1).…”
supporting
confidence: 60%
“…As SIZ proteins are also conserved in plants (Figure 3), it is likely that the heterologous overexpression of SIZ enhances cold tolerance in plants. Recently, it was reported that the expression of rice OsSIZ1 resulted in tolerance to drought and heat stresses and phosphate starvation in creeping bentgrass (Li et al 2013). Although cold tolerance was not investigated in that study, it is likely that OsSIZ1 also enhances cold tolerance, as we observed for SIZ1 (Figure 1).…”
supporting
confidence: 60%
“…Either alone, or with the help of E3 ligases, SCE links the SUMO carboxyl terminus to lysine e-amino groups in the substrate. Analysis of mutants suggests that SUMO conjugation is important for responses to a variety of stresses including drought, low temperature, and pathogens (Catala et al, 2007;Conti et al, 2008;Lee et al, 2007;Miura et al, 2007Miura et al, , 2012Zheng et al, 2012;Li et al, 2013;Zhang et al, 2013) and that sumoylation affects developmental processes such as growth, initiation of flowering, meristem maintenance, gametophyte development, and root architecture (Murtas et al, 2003;Ishida et al, 2009Ishida et al, , 2012van den Burg et al, 2010;Miura et al, 2011;Thangasamy et al, 2011;Ling et al, 2012;Elrouby et al, 2013;Conti et al, 2014;Son et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Under drought and high temperature stresses, OsSIZ1-overexpressing plants presented higher performance than wild-type plants, showing a stronger growth of the root, higher water retention and higher cell membrane integrity. 37 Another study verified that OsPUB15 (Plant U-box 15) overexpression, which encodes a cytosolic protein from class II PUB family that contains a U-box domain, is regulated by environmental stresses. 40 Plant proteins that contain a U-box domain belong to the E3 ligase family that assists the poly-ubiquitination of target proteins in degradation or mono-ubiquitination and subsequent modification of the target proteins localization or activity.…”
Section: Genes Involved In Multiple Abiotic Stressesmentioning
confidence: 94%
“…7 The post-translational modification process called SUMOylation, which involves the function of SUMO (Small Ubiquitinrelated MOdifier), is considered an important protein regulatory pathway, which occurs by the conjugation of small modifiers related to ubiquitin. 36,37 SUMOylation modulates protein stability, enabling the regulation of several cell processes, such as the enzymatic activity and environmental stress responses in plants. 37,38 Several potential targets of SUMOylation were identified, including proteins involved in the regulation of low temperature responses.…”
Section: Heavy Metal Stressmentioning
confidence: 99%
See 1 more Smart Citation